Application of GaN in 5G Technology. (November 2020) - Wang, Kun; Sheng, Chenxu
Abstract: With the progress of informatization, the development of communication technology and the wide application of wide bandgap semiconductors represented by GaN, the application of GaN in 5G technology has received increasing attention. In this paper, various characteristics of GaN application in 5G technology were emphatically introduced and a detailed analysis of these characteristics was conducted on the basis of the GaN application in 5G technology via literature searching and combining what we have learned. In addition, the development and innovation of GaN power devices in recent decades and some problems encountered at the present stage were explained and a certain prediction of the GaN application in 5G technology were proposed that this area will be a great part of industry in 21th century.